2015
DOI: 10.3399/bjgp15x686125
|View full text |Cite
|
Sign up to set email alerts
|

Depth of the patient–doctor relationship and content of general practice consultations: cross-sectional study

Abstract: BackgroundPatient-doctor continuity is valued by both parties, yet the effect of the depth of the patient-doctor relationship on the content of consultations in general practice is unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 24 publications
0
21
0
3
Order By: Relevance
“…9,10 Additionally, previous research supports participants' perceptions that a healthy doctor-patient relationship facilitates patient disclosure of sensitive information and compliance. [11][12][13] Research also suggests that this relationship increases patient satisfaction and may improve clinical outcomes. [14][15][16] The importance of personal aspects of the doctor-patient relationship featured prominently in these results.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Additionally, previous research supports participants' perceptions that a healthy doctor-patient relationship facilitates patient disclosure of sensitive information and compliance. [11][12][13] Research also suggests that this relationship increases patient satisfaction and may improve clinical outcomes. [14][15][16] The importance of personal aspects of the doctor-patient relationship featured prominently in these results.…”
Section: Discussionmentioning
confidence: 99%
“…The depth is a product of the dynamic factors of longitudinal care and consultation experiences, and encompasses what the patients consider to be mutual knowledge, trust, loyalty and regard between the patient and the doctor. A recent study [36] found that the depth of the doctor–patient relationship, as Ridd et al [35] define it, is associated with more topics raised by the patient and more discussion on emotional and psychological issues in consultations. Skirbekk et al [37], in their studies of patients’ consultations with GPs, interpret trust as the patient’s implicit willingness to accept the physician’s judgement in matters of concern to the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative research might help us understand how, when, and why continuity of care influences health care use, shedding light on factors such as consultation skills of the general practitioner, physician knowledge of patients, patient trust in the physician and his/her abilities, and patient feelings of loyalty toward the physician. [39][40][41] The introduction in 2014 of a "named general practitioner" who is responsible for the health care for each patient aged 75 and older offers the opportunity to investigate whether this intervention indeed has resulted in better longitudinal continuity of care and in reduced hospital admission.…”
Section: Implications For General Practices and Future Researchmentioning
confidence: 99%